Carbon Ion Radiotherapy for Prostate Cancer: Current Status in Japan. (October 2020) - Tsuji, H
Abstract: Clinical trials on carbon ion radiotherapy (C-ion RT) for the prostate cancer were conducted at the NIRS for over 20 years. The results so far have been quite satisfactory in both toxicity and tumour control. In addition, advancement of hypofractionation has been successfully progressed and 12-fraction C-ion RT could be established. To obtain the outcomes of multi-institutional clinical trials, a study group, J-CROS, was organized and conducts several multicenter clinical trials including the prospective study for the high-risk prostate cancer. It is expected that the outcomes of these clinical studies would result in widening the coverage of National Health Insurance for the C-ion RT. Technical progression has been also achieved at the NIRS. The scanning irradiation became available in 2011 and all the prostate cancers are treated with scanning at present. A new clinical trial of 4-fraction C-ion RT for the locally recurrent prostate cancer has been started using dose painting of scanning beam. The rotating gantry of heavy ion beam was also installed. These technical progressions enable to perform the intensity modulated ion therapy with carbon beam alone or with various ion species.